Characterization of a regiospecific epivancosaminyl transferase GtfA and enzymatic reconstitution of the antibiotic chloroeremomycin - Lu, Wei (National Academy of Sciences, 2004)
Chloroeremomycin, a vancomycin family glycopeptide antibiotic has three sugars, one d-glucose and two l-4-epi-vancosamines, attached to the crosslinked heptapeptide backbone by three glycosyltransferases, GtfA, -B, and -C. Prior efforts have revealed that GtfB and -C in tandem build an epivancosaminyl-1,2-glucosyldisaccharide chain on residue 4 of the aglycone; however, the characterization of GtfA and glycosylation sequence of chloroeremomycin have been lacking. Here, we report the expression and purification of GtfA, as well as synthesis of its sugar donor, 2′-deoxy-thymidine 5′-diphosphate (dTDP)-β-l-4-epi-vancosamine. GtfA transfers 4-epi-vancosamine from the chemically synthesized dTDP-4-epi-vancosamine to the β-OH-Tyr(6) residue of the aglycone, preferentially after GtfB action, to generate chloroorienticin B. With the preferred kinetic order of GtfB, then GtfA, then GtfC established, we have succeeded in reconstitution of chloroeremomycin from the heptapeptide aglycone by the sequential actions of the three enzymes.